2019
DOI: 10.1177/1087054719892887
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Rich Club Organization in Hemispheric White Matter Networks of ADHD

Abstract: Objective: Brain network studies have revealed abnormal topology asymmetry of white matter (WM) in ADHD. Recently, rich club organization was proposed to be a key feature of brain network topology. However, abnormalities in the rich club organization of hemispheric WM networks in ADHD remain unclear. Method: Forty ADHD patients and 51 normal controls participated in this study. Structural networks were reconstructed based on diffusion tensor imaging (DTI) and analyzed with graph theory. Results: The two groups… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 61 publications
0
24
0
Order By: Relevance
“…Wang et al (2021) found that hub regions of ADHD included the INS, the MOG, the CAU, and the PUT. Li, Cui et al (2021) also found hub regions of ADHD including the MOG, INS, and PUT. These hub regions are largely consistent with our studies.…”
Section: Increased Connector Hub In Adhdmentioning
confidence: 86%
See 2 more Smart Citations
“…Wang et al (2021) found that hub regions of ADHD included the INS, the MOG, the CAU, and the PUT. Li, Cui et al (2021) also found hub regions of ADHD including the MOG, INS, and PUT. These hub regions are largely consistent with our studies.…”
Section: Increased Connector Hub In Adhdmentioning
confidence: 86%
“…We already know that ADHD has abnormal connection in the PHG.L (Carmona et al, 2005). Li, Cui et al (2021) revealed the functional connection enhancement of the PHG.L in ADHD. D 'Agati et al (2010) found abnormalities in the SMA.…”
Section: Increased Pc and Decreased Q In Adhdmentioning
confidence: 98%
See 1 more Smart Citation
“…Three kinds of connections could be defined after dividing the brain regions into rich club and non-rich club nodes: Rich club connections between rich club nodes, feeder connections linking rich club nodes and non-rich club nodes, and local connections between non-rich club nodes ( van den Heuvel et al, 2013 , Wang et al, 2018 ). To examine the three types of connections in the whole brain, connection strength was calculated for each of the three types ( Li et al, 2019 , Sa de Almeida et al, 2021 ). The Rich-club connection strength is equivalent to the sum of reconstructed fibers between rich club nodes ( Collin et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have reported that ADHD is linked to alterations of asymmetries in the connection between the basal ganglia and frontal areas ( Silk et al, 2016 ), in the cingulum, the inferior and superior longitudinal fasciculus, the cortico-spinal tract ( Douglas et al, 2018 ), and in the posterior thalamic radiation ( Wu et al, 2020 ). Moreover, ADHD has been linked to reduced rightward asymmetry in global network efficiency ( Li et al, 2021 ). However, since none of these effects were observed in more than one study, more research on structural white matter asymmetries in ADHD is clearly needed.…”
Section: Attention Deficit Hyperactivity Disordermentioning
confidence: 99%